2009
DOI: 10.3348/kjr.2009.10.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Slot-Scan Digital Radiography of the Lower Extremities: a Comparison to Computed Radiography with Respect to Image Quality and Radiation Dose

Abstract: ObjectiveTo compare the slot-scan digital radiography (SSDR) of the lower extremity region and the computed radiography (CR) method with respect to the image quality and radiation exposure.Materials and MethodsWe enrolled 54 patients who underwent both the SSDR and CR of the lower extremities. The study evaluated and statistically compared the image quality of four features (outer cortex, inner cortex, trabeculae and intermuscular fat) at six different levels (pelvis, hip, femur, knee, tibia and ankle) between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“… 54 and Kwang et al . 55 who state doses of 687 μGy for an adult patient and 278 μGy for slot-scanning radiography, respectively.…”
Section: Resultsmentioning
confidence: 99%
“… 54 and Kwang et al . 55 who state doses of 687 μGy for an adult patient and 278 μGy for slot-scanning radiography, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The health hazard caused by the ionising radiation was minimal. 9 This study was approved by the cluster clinical research ethical committee. Written informed consent was obtained from each subject.…”
mentioning
confidence: 99%
“…Precht et al ( 6 ) used multi-frequency processing, which decomposes the image into a series of sub-frequency images and then to fuse these into one single image with optimized contrast, achieved optimal image quality at a dose reduction of 61%. In addition, with new detector designs, other studies shown improved, or maintained image quality with average dose reduction of 30% ( 7 8 ).…”
Section: Introductionmentioning
confidence: 99%